Mechanical Performance and Thermal Stability of Natural Fiber Composite Using Palm Oil Biomass - Nabinejad, Omid (Ph.D., 2017)
This Thesis demonstrates an experimental study on the development of thermoset-based natural fiber particle-reinforced composite. The overall objective was to improve the mechanical properties and investigate the thermal stability of the composite. It addresses, the effect of various chemical treatment of filler types, filler size, filler percentage and matrix type on the mechanical properties and thermal stability of the composite. To improve the mechanical performance, a hybrid composite containing carbon nanotubes was also synthesized.